Kajian Teologi Alkitabiah tentang LGBTQ dan Implikasinya bagi Gereja - Silitonga, Roedy; Sitompul, Binarwan; Lenny, Ruth; SDP, Titis Dwi (JURNAL LUXNOS, 2024)
In the context of Indonesian society, the LGBTQ community creates tensions with Christian views of the Bible's interpretation of human love and freedom. Conflicts arise between LGBTQ claims of individual freedom to express their sexual orientation and biblical teachings that emphasize moral boundaries. A strong emphasis is placed on the Christian perspective on LGBTQ issues in this paper, emphasizing the importance of understanding and applying biblical principles. Through a qualitative research method combining literature study and descriptive analysis, the arguments are developed with clarity and depth, supported by the Bible's grand narrative and specific verses. The discussion presents a comprehensive picture of the Christian view on LGBTQ, affirming that love should be shown to LGBTQ individuals without undermining the truth and will of God in the Bible. The contribution of the church in addressing this issue is emphasized, including the need to provide moral and spiritual support for individuals seeking repentance, as well as the role of the church as a place of spiritual restoration and renewal. The importance of considering biblical principles while still loving the individuals involved, thus presenting a balanced and insightful argument on the issue from a Christian perspective. Keywords: Tensions, LGBTQ Community, Christian Views, Role of the Church